Citizenship on Catfish Row : race and nation in American popular culture - Harpham, Geoffrey Galt, 1946- (University of South Carolina Press, 2022)
"Citizenship on Catfish Row: Race and Nation in American Popular Culture retrieves three "iconic" works, each of which launched an entire genre-the serious narrative film (The Birth of a Nation), the "integrated musical" (Show Boat), and American opera (Porgy and Bess), to interpret popular entertainment in the Jim Crow era. Despite their manifold differences, these radically innovative works shared two striking features: each attempted to represent the character or spirit of America in narrative form, and each included in that story a central role for the issue of race. As popular entertainment designed to appeal to audiences, these works both endorsed and helped to shape a contemporary social consensus on race that we now find grievously flawed, and each has been sharply and appropriately criticized on that account. But when read with attention to the many ways in which they seem to question, and even contradict themselves, these works appear in a very different light, not as monuments to a dishonorable past but as expressions of a conflicted and uncertain culture burdened by history but groping its way-not always with a purposeful stride, not always with clear sight, and not always in good faith-toward a present moment confident enough of its position to criticize them. By identifying the common ambition in these foundational works, Citizenship on Catfish Row enables us to see them as moments in an evolving popular understanding of American national identity. And by focusing on points of incoherence or dissonance in their telling of the national story, it suggests the impediment to national unity represented by race. Drawing attention to the ways in which popular entertainment confronted, sometimes through evasion and sometimes with a brutal honesty, the issue of race, Harpham proposes that analysis of these works can benefit our polarized and vitriolic conversation about our nation's most important problem"--